2019
DOI: 10.1021/acs.cgd.9b00111
|View full text |Cite
|
Sign up to set email alerts
|

Various Silver Phosphinate Inorganic Architectures in Three-Dimensional Frameworks with Argentophilic Interactions

Abstract: Three silver compounds with the formulas: [Ag2(HL1)] (1), [Ag10(L2)2(H2O)1.25] (2), and [Ag5(L3)]·1.5H2O (3) were obtained by self-assembly of silver nitrate with 4,4′-phosphinicobis-dibenzoic acid (H3L1), 4,4′-phosphinicobis-diisophthalic acid (H5L2), and 2,2′-phosphinicobis-diisophthalic acid (H5L3) under hydrothermal conditions. The structures of these compounds were confirmed by various characterization methods. Both 1 and 2 crystallize in P21/n space group and present three-dimensional (3D) frameworks, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…The Ag + ion has distorted tetrahedral geometry (AgO 2 N 2 ) connecting two oxygen atoms carboxylate group, one nitrogen atom of pyrazolate ligand, and one nitrogen atom of solvent moiety (Figure a and Figure S12). The respective bond lengths of Ag–O fall in the range 2.337(3)–2.481(3) Å, and Ag–N bond distances are in the range 2.237(5)–2.302(4) Å, closely matching with the earlier reported silver­(I)-based coordination compounds. , The various < O/N–Ag–O/N angles differ in the range 84.66(11)–133.69(17)° with an average of 109.03°, confirming the distorted tetrahedral geometry of the Ag ion. The important bond lengths and angles are supplied in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…The Ag + ion has distorted tetrahedral geometry (AgO 2 N 2 ) connecting two oxygen atoms carboxylate group, one nitrogen atom of pyrazolate ligand, and one nitrogen atom of solvent moiety (Figure a and Figure S12). The respective bond lengths of Ag–O fall in the range 2.337(3)–2.481(3) Å, and Ag–N bond distances are in the range 2.237(5)–2.302(4) Å, closely matching with the earlier reported silver­(I)-based coordination compounds. , The various < O/N–Ag–O/N angles differ in the range 84.66(11)–133.69(17)° with an average of 109.03°, confirming the distorted tetrahedral geometry of the Ag ion. The important bond lengths and angles are supplied in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…6 Lu et al reported the synthesis of three silver coordination polymers by coordinating three pyridine carboxylic hydrazide (4-pyridine carboxylic hydrazide, 3-pyridine carboxylic hydrazide, and 2-carboxylic hydrazide) with silver nanoclusters, which present green emission upon the excitation of UV light. 7 Ashenfelter et al synthesized molecular Ag-glutathione compounds of Ag 32 (SG) 19 , Ag 15 (SG) 11 , and Ag 11 (SG) 7 , which emit red light upon the excitation of blue light. 8 Xie et al made silver-organic gels (NH4) 9 [Ag 9 (mba) 9 ], which undergo the aggregation-induced emission of red light and fluorescence-to-phosphorescence switching.…”
Section: Introductionmentioning
confidence: 99%
“…He et al synthesized three kinds of silver phosphinate in three-dimensional frameworks with argentophilic interactions, which reveal a green emission upon blue light excitation. 11 Shu et al used Pb ions to modify Ag 2 S quantum dots for tuning its emission in the second nearinfrared window. 12 Samarium-based compounds have been another class of interesting fluorophores because of their orange/red light emission, 13−18 reports showing that Sm-based compounds can emit fluorescence other than orange/red light.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations